Observation of Bothrops atrox Snake Envenoming Blister Formation from Five Patients: Pathophysiological Insights - Sarah N. C. Gimenes (MDPI AG, 2021)
In the Brazilian Amazon, Bothrops atrox snakebites are frequent, and patients develop tissue damage with blisters sometimes observed in the proximity of the wound. Antivenoms do not seem to impact blister formation, raising questions regarding the mechanisms underlying blister formation. Here, we launched a clinical and laboratory-based study including five patients who followed and were treated by the standard clinical protocols. Blister fluids were collected for proteomic analyses and molecular assessment of the presence of venom and antivenom. Although this was a small patient sample, there appeared to be a correlation between the time of blister appearance (shorter) and the amount of venom present in the serum (higher). Of particular interest was the biochemical identification of both venom and antivenom in all blister fluids. From the proteomic analysis of the blister fluids, all were observed to be a rich source of damage-associated molecular patterns (DAMPs), immunomodulators, and matrix metalloproteinase-9 (MMP-9), suggesting that the mechanisms by which blisters are formed includes the toxins very early in envenomation and continue even after antivenom treatment, due to the pro-inflammatory molecules generated by the toxins in the first moments after envenomings, indicating the need for local treatments with anti-inflammatory drugs plus toxin inhibitors to prevent the severity of the wounds.